Trends in New Zealand climate change policy 1988 - 2006 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Public Policy at Massey University - Harbrow, Malcolm Robert (Massey University, 2007)
Since 1988 the New Zealand government has participated in an international effort to limit climate change. This study focuses on the domestic policies to reduce greenhouse gas emissions pursued over the period 1988 - 2006, using information drawn from public sources and obtained under the Official Information Act. The science of climate change, international legal framework, and New Zealand's emissions are briefly described to provide the context for policy. The history of domestic climate change policy between 1988 and 2005 is reviewed, and the policies released over the course of 2006 examined. The long-term trends in policy are analysed, and the 2006 policy assessed against them to determine whether it represents a continuation or departure from those trends. Finally, some brief policy recommendations are made. The analysis of long-term trends shows that the New Zealand government has consistently preferred economic instruments over regulatory ones in the effort to reduce emissions, and that it has consistently excluded agriculture from policy. There has also been a heavy reliance on forest sinks at the expense of emissions reductions. Finally, there has been a repeated failure to implement policy, particularly in the area of putting a price on carbon. The 2006 policies broadly followed these trends, although with some important differences: there was a greater willingness to use regulation and the first steps towards incorporating agriculture were taken. Overall, the approach was more pragmatic than that taken previously.
Keywords: New Zealand; Climatic changes; Government policy; Environmental policy; Global warming